Effect of Pectin Biodegradation with Aspergillus niger on Total Flavonoid Content of Citrus limon L.) - Abduh, Muhammad Yusuf; Zuliansyah, Wahyu; Aprina, Lestari; Arazella, Natalie (Jurnal Biodjati, 2019)
Lemon peel and leaf as well as lower grade of lemon contain a considerable amount of flavonoid which can be extracted to produce a valuable product. The presence of pectin in lemon hinders the extraction of flavonoid compound. This research was conducted to examine the effect of pectin biodegradation of lemon leaf, peel, and lower grade fruit using solid-state fermentation towards the yield of pectin, crude flavonoid, and total flavonoid content. Fermentation was carried out with the help of Aspergillus niger at 30℃ for 3, 5, 7, and 9 days of cultivation time. Pectin was extracted from the fermentation broth using citric acid. Crude flavonoid was extracted using maceration and stirred about 500 rpm at 50℃ for 40 minutes. Total flavonoid content was analyzed using a spectrophotometer. The optimum cultivation time of Aspergillus niger with leaf and peel was 9 days with a pectin yield from lemon leaf was 0.43% dry weight and the pectin yield from lemon peel was 0.04% dry weight. As for the lower grade fruit, a cultivation time for 7 days showed an optimal result with a pectin yield of 0.08% dry weight. The total flavonoid content in the leaf increased up to 94.3% (1.06 mg of the quercetin equivalents per g of substrate) whereas the total flavonoid content in the peel and lower grade fruit increased up to 42% (0.12 mg of the quercetin equivalents per g of substrate) and 48% (0.021 mg of the quercetin equivalents per g of substrate), respectively. These results highlighted the potential valorization of Citrus limon L. as an alternative source for producing flavonoid in food and pharmaceutical industry.